Comparativo de líneas promisorias y variedades comerciales de Arroz (Oryza sativa) bajo riego en Yurimaguas - Crisologo Cortegana, Walker (2000)
Was proposed as main objective, evaluate and select lines and varieties of rice coa good agronomic characteristics, high yield potential and good milling quality. Under a completely randomized block design with four replications, they were evaluated 05 promising lines and 04 commercial varieties; all from the experimental station "El Porvenir" Juan Guerra-Tarapoto. The experiment was conducted under conditions of tropical rain forest, in the village of Qtúnayac district of Yurimaguas, Province of Alto Amazonas, Loreto Department; loe between 5 ° 59 '17 "south latitude and 76 ° 10' 26" west longitude 177 HLS.ILm. Planting seedbed for all study components (lines and varieties), was held on February 5, 1999 (in seedbeds pools); pure transplant the same was held on 07 and 08 March at 0.25 m spacings. by 0.25 between strokes. The final field fertilization was performed with a dose of 90 kg N / ha. Urea using only 46% of wealth as a source of nitrogen; the same that applied in installments, 50 kg at 10 days after transplantation and 40 kg at the beginning of encofinado or "cotton knit" for lines and varieties; The harvest took place between 134 and 156 days after planting , as each of the treatments showed adequate harvest ripening. The highest yield was achieved by the control variety T9 (Inia-14} with 6286 Timba, followed by varieties witness T8 (Porvenir 95) and T7 (Capirona), with June 2919 and 5475 t / ha respectively. Also their performance was highlighted by the promising line T4 (PNA 2002-HU4-EP1-1) 5 3454 Tm / ha of grain